A promoção da Accountability e do controle finalístico nos projetos executados pelas fundações de apoio em parceria com as IFES : um estudo da atuação do Ministério da Transparência e Controladoria Geral da União - Pinto, Vannildo Cardoso (2018)
This study, a descriptive research, has a quantitative and qualitative approach to understand how Ministério da Transparência e Controladoria Geral da União (CGU), the central body of the internal control system of the Federal Executive Branch, ensures accountability and purpose control of projects executed by the support foundations in partnership with the federal higher education institutions (Ifes). To enable a better comprehension, categorical analysis was used on the audit reports, the main type of document made by the Authority when it comes to control of such partnerships, that were uploaded on the Internet between January 2013 and February 2018. Through this analysis, were found that CGU is very focused on accountability and quite limited in terms of purpose control of the partnerships between the Ifes and the supporting foundations.After this diagnosis, five proposals were elaborated that aim to improve the performance of CGU in the exercise of accountability and purpose control over the support foundations, when they execute projects in partnership with the Ifes, in addition to having been suggested to update the text of the Decree 7,423 / 2010, which is the regulation of Law No. 8.958 / 1994, which governs the relationship between the Ifes and the support foundations.For future studies, we suggest a systematic review of the literature on the relationship between the different types of public institutions of higher education and science and technology and the support foundations, as well as further studies on the performance of control agencies, not only federal, on this relationship.